The Influence of Cost per Mille and Cost per View on Profitability: A Management Accounting Study in Digital Advertising - Nurita Elfani Prasetyaningrum; Ramadhian Agus Triono Sudalyo (Jurnal Ilmiah Akuntansi dan Bisnis, 2026)
This research examines the extent to which digital advertising payment models—specifically Cost per Mille (CPM) and Cost per View (CPV)—influence firm profitability from a management accounting perspective. Adopting a quantitative research design, the study analyses panel data drawn from 100 companies operating in Central Java Province, Indonesia, across three key sectors—e-commerce, financial services, and retail—over the period 2022 to 2024. The empirical analysis employs a dynamic panel data framework estimated using the Generalized Method of Moments (GMM). The findings indicate that CPM is more effective in enhancing short-term contribution margins, while CPV exhibits a stronger association with customer lifetime value. Firms that adopt a more balanced allocation between CPM- and CPV-based advertising tend to report higher net profit margins than those relying predominantly on a single payment model. Moreover, the effectiveness of each advertising model varies across industry sectors and firm size, with the intensity of market competition moderating the relationship between CPV and profitability. This study contributes to the management accounting literature by offering a profitability-oriented framework for evaluating digital advertising payment models and by demonstrating how alternative advertising cost structures shape firm performance.